Evaluasi Kebijakan Standar Pelayanan Fisioterapi di RSUD Prof Dr. H.M. Chatib Quzwain Kabupaten Sarolangun - Ginting, Edna Rodes; Kasim, Felix; Bangun, Imelda (Jurnal Akademika Baiturrahim Jambi, 2024)
Physiotherapy Service Standards are guidelines that must be followed by physiotherapists in performing physiotherapy services. The standard policy needs to be evaluated for its application at least every 2 years and a maximum of 4 years as an effort to equalize and improve the quality of health services. The adjustment of existing service standards in accordance with the classification of health facilities has been regulated in PMK Number 65 Year 2015. The physiotherapy service standards referred to are listed in article 3 (three), including service delivery, service management and resources. This research uses descriptive qualitative methods. The number of samples or informants in this study were 14 people consisting of the Director of the Hospital (1 person), Head of Medical Services (1 person), Physiotherapy Implementers (6 people), and Physiotherapy Patients (6 people). Data were collected through observation, checklist sheets and interviews with informants.  Based on the results of this study, it can be concluded that the Physiotherapy Service Standards Policy at RSUD Prof. Dr. H.M. Chatib Quzwain Sarolangun Regency is not optimal, seen from the dimensions of service management: not yet integrated and needs to be improved according to applicable standards, including through procurement / increasing the number of supporting tools for physiotherapy services. In addition, digital-based administration needs to be improved to support the implementation of coordination, integration and synchronization as an effort to achieve professional, comprehensive and integrated, equitable and sustainable physiotherapy services. Furthermore, in the resource dimension, the unavailability of a doctor in the physiotherapy unit has an impact on the performance of the unit and the quality of physiotherapy services at RSUD Chatib Quzwain